Microbial surface-active substances as antiadhesive agents - Pirog, Tatiana; Savenko, Inga; Lutsay, Dariya (My University, 2016)
The literature data of recent years about capacity of biosurfactants synthesized by bacteria (Pseudomonas, Lactobacillus, Bacillus) and fungi (Candida, Trichosporon, Saccharomyces) not only to avert the adhesion of microorganisms on the different materials, but also to destroy formed biofilms on them were presented. The perspective of biosurfactants to prevent pathogens colonization on biotic and abiotic surfaces, that is known, can be a reason of cause and spread of infectious diseases was discussed. The data of our researches about antiadhesive properties of biosurfactants synthesized by Acinetobacter calcoaceticus IMV B-7241, Nocardia vaccinii IMV B-7405 and Rhodococcus erythropolis IMV Ac-5017 were presented.
Keywords: кафедра біотехнології і мікробіології; microbial adhesion; biofilm disruption; поверхнево-активні речовини; адгезія; руйнування біоплівки